Review of “The Problem of Order in the Global Age“ (Andreas Pickel) - Fuchs, Christian (tripleC)

A Contribution to Critical Globalization Studies. Centre for the Critical Study of Global Power and Politics Working Paper CSGP 09/8 - Fuchs, Christian

Gas sensor based on ordered mesoporous In2O3 - Wagner, T.; Sauerwald, T.; Kohl, C.-D.; Waitz, T.; Weidmann, C.; Tiemann, Michael (Thin Solid Films)
We present the preparation of a semiconductor gas sensor based on ordered mesoporous In2O3. The In2O3 was synthesized by structure replication procedure from cubic KIT-6 silica. A detailed analysis of the morphology of the mesoporous powders as well as of the prepared sensing layer will be shown. Unique properties arise from the synthesis method of structure replication such as well defined porosity in the mesoporous regime and nanocrystallites with high thermal stability up to 450 °C. These properties are useful for the application in semiconducting gas sensors. Test measurements show sensitivity to methane gas in concentrations relevant for explosion prevention.

Halbleitende Metalloxide als Gassensoren im Chemieunterricht - Waitz, Thomas; Tiemann, Michael (CHEMKON)
Halbleitende Metalloxid-Gassensoren werden sowohl im industriellen Bereich als auch im Haushalt zur Luftüberwachung verwendet. Die Funktionsweise basiert auf einer reversiblen Änderung des Sensorwiderstandes in Anwesenheit sowohl oxidierender als auch reduzierender Gase, die mit einfachen Mitteln gemessen werden kann. In diesem Artikel wird vorgestellt, wie sich die bei der Gasdetektion ablaufenden Vorgänge mit Hilfe des Ionosorptionsmodells in Kombination mit einem einfachen Festkörperbändermodell deuten lassen. Abschließend werden einfache, im Chemieunterricht zu realisierende Experimente mit Gassensoren präsentiert.

Autonomous Sensor Nodes for Aircraft Structural Health Monitoring - Becker, Thomas; Kluge, Martin; Schalk, Josef; Tiplady, Keith; Paget, Christophe; Hilleringmann, Ulrich; Otterpohl, Tobias (IEEE Sensors Journal)
Keywords: Electrical and Electronic Engineering; Instrumentation

Efficient Antenna Design of Inductive Coupled RFID-Systems with High Power Demand - Reinhold, Christian; Scholz, Peter; John, Werner; Hilleringmann, Ulrich (Journal of Communications)
Keywords: Electrical and Electronic Engineering

N-type single nanoparticle ZnO transistors processed at low temperature - Wolff, Karsten; Hilleringmann, Ulrich (2009 Proceedings of the European Solid State Device Research Conference)

Lock Detection for Charge-Pump Phase-Locked Loops - Wiegand, C; Hedayat, C; Hilleringmann, Ulrich (Sophia Antipolis Microelectronics SAME)

Finite symplectic matrix groups (Dissertation) - Kirschmer, Markus
Die invarianten Formen aus dem Anhang sind hier verfügbar:http://www.math.rwth-aachen.de/homes/Markus.Kirschmer/symplectic/

von der Leyen zu Bloemersheim, Friedrich Heinrich Freiherr (1769-1825) - Schroeter-Wittke, Harald (Protestantische Profile im Ruhrgebiet. Fünfhundert Lebensbilder aus fünf Jahrhunderten)